Developing and Managing a Community Outreach and Dissemination (COD) Core for a multi-institution grant project - Angela B. Lindsey; Nadia Bahadori; Samantha Goldenberg (EDIS, 2018)
Outreach and engagement cores have become more and more popular with grant and project requests. This EDIS discusses the steps in developing a community outreach and dissemination team for a large grant project. This includes discussing the role of the core in meeting the goals of the project while keeping targeted communities informed and involved in the project.